2019
DOI: 10.1163/15707563-18000003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between frugivorous vertebrates and two plant species of the genus Spondias

Abstract: Most plant species in the Atlantic Forest invest in zoochory as a dispersal mechanism and many depend on vertebrates to fulfill that role. The sizes of fruits and seeds are limiting factors in interactions between vertebrates and plant species. For example, plants that produce fruits with large seeds are more dependent on large frugivorous vertebrates for dispersal. We used camera traps to observe the interactions between frugivorous vertebrates and two large seed-producing plants of the genus Spondias in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Studies have confirmed that birds highly prefer fruits with red colour (Larrinaga, 2011;Pires et al, 2018), while mammals feed on fruits of various colours (Bollen et al, 2004;Koike and Masaki, 2019). The sizes of fruits and seeds are limiting factors in interactions between vertebrates and plant species (Sampaio et al, 2018). Our observations also showed that S. guttata had a limited avian species assemblage.…”
Section: Species L Analysis Articlesupporting
confidence: 74%
“…Studies have confirmed that birds highly prefer fruits with red colour (Larrinaga, 2011;Pires et al, 2018), while mammals feed on fruits of various colours (Bollen et al, 2004;Koike and Masaki, 2019). The sizes of fruits and seeds are limiting factors in interactions between vertebrates and plant species (Sampaio et al, 2018). Our observations also showed that S. guttata had a limited avian species assemblage.…”
Section: Species L Analysis Articlesupporting
confidence: 74%
“…Importance of this resource for animals is evidenced by the fact that when marked drops in fruit availability occur, as those associated with climate fluctuations such as El Niño, mortality among the fauna can drastically increase due to famine (Wright et al 1999). A large proportion of fruits are consumed in situ (in the tree canopy) or taken by animals to be consumed elsewhere (Bonaccorso et al 1980;Jayasekara et al 2007;Sampaio et al 2019). As a consequence of this or by mere gravity, a significant amount of fruits falls and accumulate at the base of trees.…”
Section: Introductionmentioning
confidence: 99%
“…Most of our current knowledge of frugivory interactions concentrates on primates, bats and birds foraging in the canopy (Sridhara et al 2016). In comparison, much less is known about the patterns of activity of medium and large body-sized mammals consuming fruits on the floor of tropical forest (but see Miura 1997; Camargo-Sanabria and Mendoza 2016; Sampaio et al 2019). Yet, mammals in this group barbara), striped hog-nosed skunk (Conepatus semistriatus) and white-nosed coati (Nasua narica;Medellin 1994).…”
Section: Introductionmentioning
confidence: 99%